2016
DOI: 10.2319/092415-647.1
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional accuracy of ceramic self-ligating brackets and estimates of theoretical torsional play

Abstract: Objective: To ascertain the dimensional accuracies of some commonly used ceramic self-ligation brackets and the amount of torsional play in various bracket-archwire combinations. Results: In all bracket systems, the slot tops were significantly wider than the slot bases (P , .001), yielding a divergent slot profile. Clarity-SLs (3M Unitek, Monrovia, Calif) showed the greatest divergence among the 0.022-inch brackets, and Clippy-Cs (Tomy, Futaba, Fukushima, Japan) among the 0.018-inch brackets. The Damon Clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
(16 reference statements)
1
8
0
7
Order By: Relevance
“…Lee et al selected seven types of 0.018 and 0.022‐in. ceramic self‐ligating brackets and observed that the slot dimensions of the different bracket systems significantly differed from each other (Lee, Lee, & Kim, ). All brackets presented a divergent profile with a slot face wider than the given value in all types of brackets.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al selected seven types of 0.018 and 0.022‐in. ceramic self‐ligating brackets and observed that the slot dimensions of the different bracket systems significantly differed from each other (Lee, Lee, & Kim, ). All brackets presented a divergent profile with a slot face wider than the given value in all types of brackets.…”
Section: Discussionmentioning
confidence: 99%
“…2); all papers from PubMed were repeated in Google Scholar. Thus the results of measurements of bracket slots have been provided in few publications [2,6,7,8,9,10,11,12,13,14,15,16,17]. The study material, methods and results of measurements by authors of each study have been provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the papers included in the review have used various methods of measurement. The equipment used comprised: one-axis light microscope [6], scanning electron microscope [7,8], stereomicroscope [9], electron microscope [9], zamka) i orthodontic bracket slot dimension (wymiar szczeliny zamka ortodontycznego).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations